Viking Jewellery Mould Making. Experimental and Reconstructive Aspects - Anders Söderberg (EXARC Journal)
Craftsmanship relies upon the silent knowledge of the skilled experience of the creative workings of the hands, a knowledge that is difficult to convert to written characters without creating a blur of words that make very little sense. Theoretical reasoning lacks the dialogue with, and the resistance from, the raw material. Making up a picture of how wax, clay and metal would behave without practical experience of them is next to impossible. You must work with the material directly to get proper answers. After nearly 600 recorded castings with reconstructed early medieval casting technology behind me, and just as many unrecorded, I may perhaps consider myself a craftsman almost as much as I am an archaeologist, and I would like to share a little of what I have learned from these experiences.